2017
DOI: 10.3389/fneur.2017.00478
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Safety of Craniotomy for Resection of Primary Central Nervous System Lymphoma: A Nationwide Inpatient Sample Analysis

Abstract: BackgroundUnlike many other central nervous system (CNS) tumors, the surgical management of primary central nervous system lymphomas (PCNSL) is traditionally limited by diagnostic biopsy. Studies that predate the use of modern neurosurgical techniques have reported a prohibitive operative morbidity for this surgery. These early experiences have dictated the non-surgical management of PCNSL, whereas resection for cytoreduction is a mainstay of treatment in other CNS malignancies. Recent studies have suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…To better understand the pattern and mechanism of relapse, we reviewed 27 relapsed patients who attained complete response (CR), partial response (PR) or stable disease (SD) during or after first-line treatment without WBRT for newly diagnosed PCNSL in our institution. We found more than half of the patients had distant recurrence and among those reached CR patients, 9/11(82%)had distant recurrence as well, which are comparable to those described with intravenous HD-MTX (12/16, 75%) 33 and those with intra-arterial HD-MTX in conjunction with blood-brain barrier disruption (BBBD) 50 (30/37, 80%).Recently, a number of studies [51][52][53][54][55] have shown that surgery may be beneficial for PCNSL patients. It is worth noting that 8 of the 11patients who achieved CR by receiving GTR, eventually relapsed with DR, which reminds us that there may be subclinical CNS lymphomas which contrast enhanced MRI cannot to detect.…”
Section: Pcnsl Is a Rare Extra-nodal Lymphoma With Aggressive Clinicasupporting
confidence: 74%
“…To better understand the pattern and mechanism of relapse, we reviewed 27 relapsed patients who attained complete response (CR), partial response (PR) or stable disease (SD) during or after first-line treatment without WBRT for newly diagnosed PCNSL in our institution. We found more than half of the patients had distant recurrence and among those reached CR patients, 9/11(82%)had distant recurrence as well, which are comparable to those described with intravenous HD-MTX (12/16, 75%) 33 and those with intra-arterial HD-MTX in conjunction with blood-brain barrier disruption (BBBD) 50 (30/37, 80%).Recently, a number of studies [51][52][53][54][55] have shown that surgery may be beneficial for PCNSL patients. It is worth noting that 8 of the 11patients who achieved CR by receiving GTR, eventually relapsed with DR, which reminds us that there may be subclinical CNS lymphomas which contrast enhanced MRI cannot to detect.…”
Section: Pcnsl Is a Rare Extra-nodal Lymphoma With Aggressive Clinicasupporting
confidence: 74%
“…This indicates a potential selection bias, which might contribute to the observed differences in the outcomes between the resection group and the biopsy group, confounding the results. The complication rates for surgical resection and biopsy seem to be comparable [40,41]. Cloney et al [40] concluded that surgical resection of PCNSL is safe for selected patients and that the complication rate is comparable to that of other intracranial neoplasms.…”
Section: Discussionmentioning
confidence: 98%
“…However, in our study, the extent of resection may correlate with PFS. Technical advances in neurosurgery have increased the safety of PCNSL surgical resections (13,14). Therefore, we propose reconsidering tumor removal to treat a single lesion amenable to resection.…”
Section: Discussionmentioning
confidence: 99%